The World Almanac and Book of Facts 2001 - Editorial Director : McGeveran, William A., Jr. (New Jercy World Almanic Books, 2001)
Presents the year-in-review of 2000, preliminary 2000 election results, a Noted Personalities section, a color section of maps and flags, and thousands of facts and statistics on economy and business, U.S. populations and cities, science, the Internet, astronomy, each of the United States, and the nations of the world.
New York Times Bestseller
Keywords: Statistics -- Almanacs, American -- United States -- Statistics